An exploratory analysis of a gender needs assessment, gendered trait preferences, and future (trait) requirements for rice breeding in Southern Asia - Connor, Melanie; Bayot, Ruvicyn (CGIAR, 2024)
Southern Asia is one of the predominant rice-growing areas worldwide, and it has seen an increase in the release of high-yielding varieties since the Green Revolution. In recent years, the needs of farmers and consumers have changed due to population changes and changes in climatic conditions. Demand-led breeding, considering the preferences of various value chain actors, is slowly changing the heavy focus on yield improvements to include other varietal, consumer, and agronomic traits. Farmers have varying preferences depending on their production scheme, geography, and market demands. Preferences seem to be heterogeneous among farming communities and need to be specified for different sections of society. Gender-specific trait preferences have often been neglected but must be addressed by breeding programs to ensure widespread uptake of new crop varieties. In order to inform the rice breeding teams in Southern Asia about gender-specific trait preferences, a narrative literature review encompassing studies of several Southern Asian countries was conducted. In addition, the Global Market Intelligence Platform (GloMIP) was used to identify market segments that present the greatest gender inequalities in Southern Asia. Results show a dearth of studies assessing trait preferences for different genders. Most studies focus on adoption constraints, with few focusing on farmers’ preferences, and these preferences were not disaggregated by gender. In Bangladesh, results highlight the need for medium-duration varieties that are suitable for intercropping with potatoes, while in Odisha, India, farmers prefer slender grain and short-duration varieties. It becomes clear that consumers value hedonic traits such as taste and aroma. However, no measures exist to evaluate these traits objectively with thresholds that can be achieved by breeding teams.